Genetic structure and diversity between and within African and American oil palm species based on microsatellite markers - AZIS NATAWIJAYA; SINTHO W ARDIE; MUHAMAD SYUKUR; ISMAIL MASKROMO; ALEX HARTANA; SUDARSONO SUDARSONO (Society for Indonesian Biodiversity, 2019)
Abstract. Natawijaya A, Ardie SW, Syukur M, Maskromo I, Hartana A, Sudarsono S. 2019. Genetic structure and diversity between and within African and American oil palm species based on microsatellite markers. Biodiversitas 20: 1233-1240. The genus Elaeis consists of only two species, Elaeis guineensis Jacq. (the African oil palm species) and E. oleifera (HBK) Cortes (the American oil palm species). E. guineensis (E.g) is widely cultivated in southeast Asia and Africa, whereas E. oleifera (E.o) is naturally existed and cultivated in Central and South America. The objectives of this research were to analyze genetic diversity of eight groups of E.g and two groups of E.o using co-dominant genetic markers (SSRs) and evaluate their genetic structures. A total of 27 SSR loci was used to genotype a total of 128 accessions of African oil palm species (E.g) belonging to three different types (Dura, Pisifera and Tenera) and eight genetic backgrounds (Dumpy Dura and Deli Dura; Avros, Dumpy Avros, Binga, and Angola Pisifera; and Angola and Dumpy Avros Tenera) and 64 accessions of E.o collected from two different regions (Tefe and Manaus). The genotype data were used to calculate the population genetic diversity and structures for each oil palm species using the appropriate software. Results of the analysis indicated although they belonged to two different species, E.g and E.o shared many of the same SSR alleles in their genome and only contain few species-specific SSR alleles. Most of the evaluated genetic parameters were similar between E.g and E.o oil palm species but E.o has higher average number of effective allele than that of E.g. The calculated genetic variance is mostly belonged to the within-species variance source while the between species is relatively small. The phylogenetic tree and structure analysis reveal the high genetic variability among the evaluated oil palm groups which would be beneficial for future breeding program at Mekarsari Research Station. The tested E.o specific alleles were effective for identifying introgression lines between Eo × E.g // E.g carrying the E.o chromosome fragments. Therefore, these E.o specific alleles could be used in oil palm backcrossing program to monitor the introgression process.